The influence of parity judgement on the derivation process from the numerals ‘one’ and ‘two’ - Iarmolovych, Galyna (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2020)
The purpose of this research paper is to describe the relationship between the binary thinking of ancient people and the formation of the concept of number. The objects of the study are paleographic, ethno-psychological and biological studies examining the development of the counting principles and quantitative thinking of primitive men. The subject of the study are the numbers ’one’ and ‘two’, as well as their forms and derivatives in Germanic languages. The analyzed studies allow to conclude that the development of the first numerals derives from dual thinking, which is based on the ability to divide the whole into parts. The close connection to the surrounding world and the inborn parity judgement of some individuals in the Upper Paleolithic Period generates the first two numbers, hence numerals in the Proto Indo-European language. Both originate from one root, the form of which can be traced to the Proto Indo-European word ‘kwa’ as a part of the whole, i.e. two hands. Starting with the ultimate meaning of binary unified entity it split first into ‘part and whole’. Later the meaning branched even more (symmetry, completeness, contradiction, branching, merging, union, sameness, equality, repetitiveness, sequence, coherence, excessiveness, addition), creating diachronically countless derivatives of the initial ‘one’ and ‘two'. The binary nature of the Indo-European thinking had an effect on both everyday life and the religion, which was implemented in a later, pre-literate period and has been corroborated by archaeological finds. The rudimentary traces of primitive binary thinking are reflected in the contemporary realia and can be found in all languages of the Indoeuropean language group. The further research will cover the influence of the paired unity by fractionation on the allocation of subsequent numericals.